Environmental Safety of Enterprises in Wartime: Challenges of the Circular Economy - Skakun, V; Chudovska, V (Ways to Improve Construction Efficiency, 2025)
The paper substantiates that war significantly transforms the environmental, economic, technological and institutional-legal conditions for the functioning of enterprises, creating multi-level threats to their environmental and economic sustainability. It is shown that the destruction of industrial facilities, critical infrastructure facilities and waste management systems leads to the accumulation of significant volumes of hazardous and mixed waste, which cannot be promptly included in circular flows. This creates significant risks for the environment, public health and production activities of enterprises, and also makes it impossible to implement full-fledged It has been established that in conditions of military uncertainty, enterprises are forced to abandon strategic eco-innovations and return to linear production models, which increases the level of environmental threats and reduces the overall level of environmental security. It has been established that regulatory instability complicates the harmonization of national legislation with European standards of the circular economy and reduces the environmental responsibility of business. Social and organizational problems are also outlined, in particular the insufficient level of environmental culture and the decline in the motivation of enterprises to invest in circular solutions in conditions of armed conflict. Environmental security of enterprises in conditions of war requires a new, adaptive approach that takes into account the specifics of the transformation of environmental risks and restrictions. The need to develop innovative infrastructure for the processing of war waste, the formation of effective mechanisms of environmental management and the modernization of the state regulation system in the sphere of the circular economy is substantiated. Strategic guidelines for post-war recovery are proposed, which include the integration of circular models into industrial policy, strengthening the environmental responsibility of enterprises and the introduction of resource efficiency technologies.